Pengaruh Harga Dan Fasilitas Terhadap Keputusan Pembelian Pada Perumahan Griya Dulomo Indah - Nisa Masali; Melizubaida Mahmud; Ardiansyah Ardiansyah; Usman Moonti; Irwan Yantu; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The research aims to determine the effect of prices and facilities on purchase decisions of Griya Dulomo Indah Residential Real Estate. This research method. The data used were primary data obtained from distributing questionnaires to resident of Griya Dulomo Indah Residential Real Estate, with a sample of 73 respondents. At the same time, data analysis technique used multiple liniear regression. The finding denoted that partially and simultaneously, prices and facilities variable affected the purchase decisions of Griya Dulomo Indah residential real estate. The simultaneous effect of price and facilities variables on purchase decisions was 25.7% on the other hand, the partial effect of the price variable on purchase decisions was 8.40%, and the effect of the facilities variable an the purchase decision was 17.3%